A Study of transcription factor MEF2A gene polymorphisms in patients with coronary artery disease: Coronary artery disease and MEF2A gene polymorphisms - Muhammad Sulaiman, Kazhal (Cellular and Molecular Biology, 2024)
MEF2A (myocyte enhancer factor-2A) is a transcription factor of the MEF2 family. It has been recognized as the cause of coronary artery disease in the absence of any other clinical characteristic. It is involved in vascular development and is most commonly found in the coronary artery endothelium. The goal of this case-control study was to see if there was a link between polymorphisms in the MEF2A gene and coronary artery disease. A case-control study was carried out to look into the possible significance of MEF2A polymorphisms as a risk factor for coronary artery disease. This research included 225 patients and 225 healthy controls. A biochemical examination was carried out to evaluate the risk factors for developing this condition. The polymorphisms of Mef2A (1250 C > T in exon 8 and 452 G > T, 481 A > G in exon 11) were found using the PCR-RFLP technique. All identified risk variables, such as hypercholesterolemia, diabetes mellitus, and hypertriglyceridemia, were shown to be statistically significant in the current study for coronary artery disease occurrence. The most polymorphisms were found in MEF2A 1250 C > T, MEF2A 452 G > T, and MEF2A 481 A > G. The genotyping results for MEF2A 1250, MEF2A 452, and MEF2A 481 were (X2 = 2.985; P = 0.235), (X2 = 4.371; P = 0.112), and (X2 = 4.025; P = 0.134), respectively. In conclusion, we identified a much higher incidence of MEF2A in people with coronary artery disease, and MEF2A may play a crucial role in cardiovascular pathophysiology. Patients and controls had considerably different genetics and frequency of alleles.